ANALISIS PENGARUH SELEKSI DAN PENEMPATAN TERHADAP KEPUASAN KERJA DAN KINERJA APARATUR SIPIL NEGARA (ASN) (STUDI KASUS: PEMERINTAHAN KABUPATEN KEEROM) - Andi Tenriarni Rahman; Siti Haerani; Wardhani Hakim (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
Human resources are very important factor in an organization or government in providing services to the public. This study aims to determine to determine the effect of Selection and Placement Against Job Satisfaction and Performance of State Civil Apparatus (ASN) in Keerom Regency. The type of research used in this study is quantitative approach. The quantitative approach bases the study of empirical rational principles. The quantitative approach bases the study of empirical rational principles. Therefore, before doing the research the researcher must find the problems and hypotheses to be tested based on the specified criteria and path analysis tool using SPSS 24.0 for windows software. The result of this research shows that partial selection and job placement have positive and significant influence to job satisfaction, job selection and placement have positive and significant influence to job satisfaction, job selection and placement have positive and significant influence on performance, job satisfaction has positive influence and significant to performance. The job satisfaction in this research can mediate the influence of selection and job placement on the performance of State Civil Apparatus (ASN) in Keerom Regency.